Integrating Interactive Technology: A Case Study at SMP Negeri 3 Manggeng: Penelitian - Isra Miranda; Nuzulul Isna (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aimed to explore students' and teachers' experiences in using the smartboard in English learning and to identify the challenges they faced during the teaching and learning process. A qualitative research design was employed to obtain an in-depth understanding of participants' perceptions and experiences. The participants consisted of students and English teachers at SMP Negeri 3 Manggeng. Data were collected through semi-structured interviews and analyzed using qualitative content analysis with the assistance of NVivo. The findings revealed that students had positive experiences using the smartboard. They reported that the smartboard increased their motivation, created a new and more enjoyable learning experience, and helped them understand English materials more easily. Teachers also expressed positive perceptions of the smartboard, stating that it improved teaching efficiency, provided greater flexibility in presenting learning materials, and effectively supported students' learning and classroom participation. Despite these benefits, both students and teachers encountered several challenges. Students identified unstable internet connectivity and power outages as the main obstacles that interrupted learning activities. Meanwhile, teachers reported limited skills in operating the smartboard, electricity disruptions, and technical problems as the primary challenges in integrating the technology into classroom instruction.